Inhibition of calpain blocks the phagosomal escape of Listeria monocytogenes. - Gloria Lopez-Castejon (Public Library of Science (PLoS), 2012)
Listeria monocytogenes is a gram-positive facultative intracellular bacterium responsible for the food borne infection listeriosis, affecting principally the immunocompromised, the old, neonates and pregnant women. Following invasion L. monocytogenes escapes the phagosome and replicates in the cytoplasm. Phagosome escape is central to L. monocytogenes virulence and is required for initiating innate host-defence responses such as the secretion of the cytokine interleukin-1. Phagosome escape of L. monocytogenes is reported to depend upon host proteins such as γ-interferon-inducible lysosomal thiol reductase and the cystic fibrosis transmembrane conductance regulator. The host cytosolic cysteine protease calpain is required in the life cycle of numerous pathogens, and previous research reports an activation of calpain by L. monocytogenes infection. Thus we sought to determine whether host calpain was required for the virulence of L. monocytogenes. Treatment of macrophages with calpain inhibitors blocked escape of L. monocytogenes from the phagosome and consequently its proliferation within the cytosol. This was independent of any direct effect on the production of bacterial virulence factors or of a bactericidal effect. Furthermore, the secretion of interleukin-1β, a host cytokine whose secretion induced by L. monocytogenes depends upon phagosome escape, was also blocked by calpain inhibition. These data indicate that L. monocytogenes co-opts host calpain to facilitate its escape from the phagosome, and more generally, that calpain may represent a cellular Achilles heel exploited by pathogens.